Polycyclic Aromatic Hydrocarbons in the Arctic: Ob and Yenisei Estuaries and Kara Sea Shelf - Fernandes, M.B.; Sicre, Marie-Alexandrine (Estuarine, Coastal and Shelf Science, 1999)
International audience